RESCUE 1122: APPLICATION OF POISSON DISTRIBUTION - Muhammad Imran; Jamal Abdul Nasir; Syed Arif Ahmed Zaidi (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: The basic idea of the study toevaluate the probabilities of various emergencies calls that could be emerging in the enhancement of operational network and adequate polices to tackle the complex emergencies situations, so that the maximum human lives and disaster of properties could be declined. DATA: The relevant data for the present study is taken from rescue 1122 ofﬁcial website of all thirty six districts. PERIOD: 10/10/2004 to 3/2/2014. METHODS: Descriptive analyses along with Poisson distribution are carried out. Poisson probability distribution is executed by using the R programming language. RESULTS: On the basis of descriptive analysis about 85.9% calls are associated to medical (47.5%) and road accident (38.4%) emergencies. While the road accidents and medical emergencies calls are signiﬁcantly high in Gujranwala and Dera ghazi Khan Division respectively. Under Poisson distribution the chance that the patient rescued is 85%. Further the maximum emergency calls arrivals with at least 90%, 95% and 99% certainty per day are computed. CONCLUSION: The proportion of medical and road trafﬁc accidents emergencies calls are signiﬁcantly high. Prediction about emergencies calls will serve as a guide in improving rescu1122 management and operational network